Resource assessment of Bel (Aegle marmelos) and potentiality to establish its processing enterprise in Tanahun district of Nepal - Baral, K.; Upreti, B. R. (Banko Janakari, 2016)
Participatory resource assessment of Aegle marmelos was carried out in six community forests (CFs) of the Jamune VDC of Tanahun district to find out potentiality for establishing community-based A. marmelos processing enterprise in the locality. Circular sample plots of 500 square meters were laid down taking 5% sampling intensity. The DBH (Diameter at Breast Height) and height of trees on the sample plots were measured and classified them into three DBH classes (10–20 cm, 20–30 cm and more than 30 cm). The number of the fruits on the three branches of each A. marmelos tree – one lower branch, one middle branch and one top branch were counted, the average number of fruits on the three branches calculated and multiplied with the number of the branches of the tree to find out the average number of fruits per tree. By calculating the weighted mean of the three different DBH-class trees, the total number of the fruits was estimated. The study found 54,830 kg of harvestable amount of A. marmelos fruit in the studied six CFs which can produce 19190.5 kg of pulp per year. Thus, establishment of juice processing enterprise was found to be feasible in the locality. Nevertheless, some shortcomings related to the management of A. marmelos resource, such as lacking of information and management options for A. marmelos trees in the Operation Plans (OPs), lower regeneration status of A. marmelos trees, higher incidences of forest-fire and open grazing in the CFs, were also recorded. The study suggests for carrying out awareness-generating activities targeted to the CF user group members, revision of OPs and incorporation of A. marmelos resource information and management options and preparation and implementation of regeneration protection plan against forest fire and grazing. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, page: 32-37, 2016